Peace Came in the Form of a Woman : Indians and Spaniards in the Texas Borderlands - Barr, Juliana (Book collections on Project MUSE., 2007)
Revising the standard narrative of European-Indian relations in America, Juliana Barr reconstructs a world in which Indians were the dominant power and Europeans were the ones forced to accommodate, resist, and persevere.